The Level of Understanding of Female Santris in Jombang about Entrepreneurship: Implications in Education - Fanani, Achmad; Najih, Aizun; Maisarah, Maisarah; Putri, Trikaloka H.; Zaki, Muhamad; Nurcahyani, Dwi; Fauziyah, Nailul (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this study is to identify the understanding and practical skills of female students in entrepreneurship, financial management, and marketing strategies at the Jombang Islamic boarding school. This research is important as it can provide the necessary insights to develop more effective and relevant educational programs. The research method employs a quantitative survey with 100 respondents using closed-ended questionnaires. The results show a low understanding of basic concepts in entrepreneurship, financial management, and marketing strategies, with average scores of 2.30, 2.30, and 2.35, respectively. The conclusion of this study emphasizes the importance of more comprehensive education to address the current gap in the literature, encouraging a more integrated and practically oriented educational approach to prepare a generation of adaptive entrepreneurs.